IMPLEMENTASI METODE ANALITYCHAL HIERACHY PROCESS UNTUK PENGAMBILAN KEPUTUSAN PENILAIAN MURID BERPRESTASI (STUDI KASUS SMP ISLAM KEBUMEN) - Dita Novita Sari; Lailaturrohmah Lailaturrohmah; Ahmad Khumaidi; Siti Muqodimah; Trisnawati Trisnawati (Institut Informatika dan Bisnis Darmajaya, 2020)
Decision making at a school institution is very important. The principal should make a decision based on long-term calculations and thinking so that the decision to determine the academic achievement of students to be taken is not wrong. In Kebumen Islamic Middle School there are still problems in making student learning reports, to determine students who excel are only determined using report cards, there is no optimal use of student learning outcomes assessment report data, there are still difficulties in knowing the achievements of student learning activities. Using the Analytical Method Hierarchy Process can make it easier for teachers to determine student academic achievement precisely and quickly. The results of testing of the system developed using the Analytical Technical Hierachy Process model can be concluded that the system has been running properly, so that this system can be used to help the school in carrying out the selection of outstanding students. Student Decision Making System Achievement in Kebumen Islamic Middle School uses the Analytical Method Hierarchy Process, this method uses 7 criterion factors namely the average value of report cards, minimum value, total value, attendance, personality, memorization of the Qur'an, and the charter achievement. From the results of the calculation of priorities can be generated ranking of the ranks of the seven high-achieving student candidates ranked first with a priority value of 6.6416 fulfilled by candidate 1